Comparative efficacy and safety of antidiabetic agents for post-transplant diabetes mellitus: a network meta-analysis - Hu, Shanbiao; Lan, Gongbin (Frontiers in Medicine, 2025)
BackgroundPost-transplant diabetes mellitus (PTDM) significantly compromises patient and graft outcomes. Although multiple antidiabetic agents are available, their comparative efficacy and safety profiles in this population remain uncertain.MethodsA systematic literature search was performed across PubMed, Web of Science, Embase, and Cochrane Library to identify clinical trials comparing antidiabetic therapies in PTDM patients. Risk of bias was assessed, and a network meta-analysis was conducted to estimate relative treatment effects. Treatment ranking probabilities, contribution plots, and funnel plots were used to evaluate hierarchy, study influence, and publication bias, respectively.ResultsTwelve studies—including 10 randomized controlled trials (RCTs) and 2 cohort studies—encompassing 7,372 patients were analyzed. The network meta-analysis evaluated four outcomes: HbA1c, fasting plasma glucose (FPG), systolic blood pressure (SBP), and composite major adverse cardiovascular and kidney events (MACE and MAKE). Compared to placebo, insulin produced the greatest reductions in HbA1c (mean difference [MD] − 0.35, 95% CI − 0.90 to 0.20) and FPG (MD − 9.06 mmol/L, 95% CI − 18.66 to 0.53). DPP-4 inhibitors showed the most pronounced decrease in SBP (MD − 3.57 mmHg, 95% CI − 7.29 to 0.16). SGLT2 inhibitors (SGLT2i) demonstrated the strongest tendency to reduce MACE and MAKE events (MD − 1.95, 95% CI − 4.85 to 0.96). SUCRA plots indicated that insulin and SGLT2i ranked highest in glycemic control and safety profiles. Funnel plot analysis suggested a low risk of publication bias.ConclusionInsulin and SGLT2i represent the most efficacious and safest options among antidiabetic treatments for PTDM, supporting their preferential consideration in post-transplant diabetes management. Further large-scale, head-to-head trials are warranted to strengthen these findings.